Peculiarities of bronchial asthma management in children with allelic GSTT1, GSTM1 gene polymorphism - Коloskova, O. K.; Bilous, T. M.; Ivanova, L. A,; Dikal, M. V.; Kopchuk, T. G. (Journal of Education, Health and Sport, 2018)
Content of peculiarities of basic anti-inflammatory therapy and its efficacy in children with available or absent deletion polymorphism of GSTM1 and GSTT1 genes coding II phase enzymes of GSTM1 and GSTT1 xenobiotic detoxication considering their acetylation status. It is established that in patients of a school age suffering from bronchial asthma with available deletion polymorphism of GSTT1 and GSTМ1 genes associated with slow acetylation phenotype anti-inflammatory therapy should be intensified emphasizing on much higher “step” or by means of addition of other anti-inflammatory drugs. In patients without deletion polymorphism of the examined genes in terms of quick acetylation phenotype average daily doses of iGCS have a tendency to prevailing over the similar ones in patients from the groups of comparison, and their triple administration is reliably higher